ANALISIS PENETAPAN UPAH MINIMUM KABUPATEN/KOTA DI PROVINSI JAWA TENGAH 2014-2023 - Ismadiyanti Purwaning Astuti; Alvina Indri Iswara (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
Central Java is one of the provinces in Indonesia, which has a strategic role in building the national economy. However, the minimum wage in Central Java Province is the lowest in Java. This study aims to determine the effect of the Human Development Index (HDI), Labor Force Participation Rate (TPAK), and Consumer Price Index (CPI) on the determination of district / city minimum wages in Central Java in 2014-2023. This study uses panel data consisting of 35 districts / cities in Central Java Province and in the period 2014-2023 sourced from BPS Central Java. This research uses panel data regression analysis method. The results of the analysis show that HDI and TPAK have a positive and significant effect on minimum wages in Central Java, while CPI has a negative and significant effect on minimum wages in Central Java. The findings encourage the Central Java government to increase HDI by improving access to education, health and quality of life in an effort to increase people's productivity and income. The government needs to provide skills training to increase labor force participation. In addition, the government needs to pay attention to the effect of CPI on MSEs by managing inflation wisely to maintain price balance and people's purchasing power.